Wet barley distillers solids as a protein source for growing pigs - Valaja, Jarmo; Alaviuhkola, Timo; Siljander-Rasi, Hilkka (nl, 1995)
The study was conducted to evaluate the chemical composition and nutritive value of wet barley distillers solids (DS) for growing pigs. The variability in the chemical composition was assayed from ten samples of DS. The variation in chemical composition was high, dry matter (DM) ranging from 140 to 236 g kg-1, crude protein ranging from 432 to 599 g kg-1 DM and lysine ranging from 37 to 51 g (160 g N)-1. In vitro digestibility of dry matter and nitrogen was determined from DS and soyabean meal (SBM) and was found to be lower in DS than in SBM (dry matter: 0.560 vs. 0.708; nitrogen: 0.662 vs. 0.922). A growth experiment was conducted with 160 growing pigs (40 pigs in each treatment) from 25 to 105 kg live weight range. Four pigs were kept in each pen (two female and two castrated males). In four isonitrogenous and isolysineous diets, 0, 0.33, 0.66 or all SBM was replaced by DS and synthetic lysine. The daily feeding allowance was restricted to provide uniform crude protein intakes. The daily weight gain and feed conversion ratio of the pigs remained about the same when one-third of SBM was replaced by DS, but they both decreased linearly (p<0.001) when higher amounts of DS were added to the diets. Dietary DS also linearly decreased the content of lean in valuable cuts and in carcass (p<0.001). In organoleptic evaluation of meat samples no differences were found between the treatments. In conclusion, the lower performance of the pigs on DS diets was mainly a result of the high variation in chemical composition of DS, which affected the protein and amino acid supply of the pigs. The results also indicated that the quality of protein is impaired during the processing of DS.
Keywords: Ko; lihasika; rankki; tärkkelysteollisuus; oheistuote; kasvu; rehut; muuntosuhde; teuraslaatu